Regulation of cochlear hair cell function by intracellular calcium stores - Sinha, Ghanshyam P.; Frolenkov, Gregory I. (Frontiers in Cellular Neuroscience, 2024)
Introduction Mammalian hearing depends on the dual mechanosensory and motor functions of cochlear hair cells. Both these functions may be regulated by Ca2+ release from intracellular stores. However, it is still unclear how exactly intracellular Ca2+ release may affect either hair cell mechano-electrical transduction (MET) or prestin-dependent electromotility in outer hair cells (OHCs). Methods Here, we used photo-activatable (caged) compounds to generate fast increases of either Ca2+ or inositol-3-phosphate (IP3) in the cytosol of young postnatal rodent auditory hair cells, thereby stimulating either Ca2+- or IP3- induced releases of Ca2+ from intracellular stores. Fast Ca2+ imaging was used to monitor propagation of Ca2+ signals along the length of a hair cell. To access potential physiological role(s) of intracellular Ca2+ releases, we used whole cell patch clamp to record: i) OHC voltage-dependent capacitance, a known electrical correlate of prestin-based electromotility, and ii) MET currents evoked by stereocilia bundle deflections with fluid-jet. In the latter experiments, changes of mechanical stiffness of the hair bundles were also quantified from video recordings of stereocilia movements. Results Ca2+ uncaging at the OHC apex initiated Ca2+ wave propagating to the base of the cell with subsequent Ca2+ build-up there. Ca2+ uncaging at the OHC base generated long-lasting and apparently self-sustained Ca2+ responses, further confirming Ca2+-induced Ca2+ release in the OHC basal region. Photoactivated IP3 initiated a slow increase of cytosolic Ca2+ ([Ca2+]i) throughout the whole OHC, confirming the presence of slow-activated IP3-gated Ca2+ stores in OHCs. Interestingly, Ca2+ uncaging produced no effects on OHC voltage-dependent capacitance. In an OHC, the rise of [Ca2+]i is known to decrease axial stiffness of the cell and may modulate the stiffness of mechanosensory stereocilia bundles. To separate these two phenomena, we explored the potential effects of intracellular Ca2+ release on mechanical properties of stereocilia bundles in cochlear inner hair cells (IHCs). Ca2+ uncaging at the apex of an IHC caused a long-lasting increase in mechanical stiffness of stereocilia bundle without any changes in the amplitude or deflection sensitivity of the MET current. Discussion We concluded that the most likely physiological role of IP3-gated Ca2+ release at the apex of the cell is the regulation of hair bundle stiffness. In contrast, Ca2+-induced Ca2+ release at the base of OHCs seems to regulate axial stiffness of the cells and its hyperpolarization in response to efferent stimuli, without direct effects on the OHC prestin-based membrane motors.